PENGARUH IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH (SIMDA), KUALITAS SUMBER DAYA MANUSIA, PENERAPAN STANDAR AKUNTANSI DAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - L, Lynda; Asnawi, Meinarni; Pangayow, Bill J. C. (Jurnal Akuntansi, Audit, dan Aset, 2019)
The research entitled "The Influence Of The Implementation Of Regional Financial ManagementInformation Systems, The Quality Of Human Resources, The Application Of Accounting StandardsAnd Government’s Internal Control System On The Quality Of Regional Financial Reports" aims toidentify to study how the quality of human resources, the implementation of regional financialmanagement information systems, the application of accounting standards, and the government’sinternal control system whether simultaneously or partially affecting the quality of regionalfinancial reports of Pegunungan Bintang regency. The causal approaches were used to analyze theconnection between independent and dependent variables or others. While the Multiple LinearRegression Analysis as an analysis tool in this study was used to measure the effect of independentvariables on the dependent variable. The result of this study indicates that the implementation ofregional financial management information systems (X1) has 2,845 with a significant level of 0,006,which means the implementation of regional financial management information systems has asignificant influence on the quality of regional financial reports of Pegunungan Bintang regency.Meanwhile, the independent variable of the quality of human resources (X2) has 3,084 with 0,003significance level, it explains that the quality of human resources has impacted significantly on thequality of regional financial reports of Pegunungan Bintang regency. As long as, the applications ofaccounting standard (X3) have a significant effect on the quality of regional financial reports ofPegunungan Bintang regency with 3,454 and 0,001 significance level. Furthermore, theGovernment’s Internal Control System variable (X4) with a value of 2,487 and a significant level of0,015, that indicates, the Government’s Internal Control System variable has significantly affected thequality of financial reports of Pegunungan Bintang regency. While the value of F measurement hasgreater than the value of F table (29,165>5,921), which explains that the quality of humanresources, the implementation of regional financial management information systems, theapplication of accounting standards and government’s internal control system simultaneously havea significant effect on the quality of regional financial reports of Pegunungan Bintang regency.